Screening tools for evaluation of depression in Chronic Obstructive Pulmonary Disease (COPD). A systematic review. Issue 1 (1st January 2017) - Bock, K.; Bendstrup, E.; Hilberg, O.; Løkke, A.
ABSTRACT: Background : Anxiety and depression are common comorbid disorders in patients with chronic obstructive pulmonary disease (COPD), though estimates of their prevalence vary considerably. Depressive symptoms/depression are important comorbidities in COPD and an increasing interest is shown to these disorders. Depression may lead to reduced quality of life and increased morbidity and mortality. These statements underline the importance of implementing the use of screening instruments for depressive symptoms in a clinical setting. This systematic review evaluates four commonly used screening tools for depression in COPD. Furthermore we assess the prevalence of depression in COPD in the evaluated studies. Design : A literature search identified studies dealing with screening for depression in patients with COPD. We focused on the instruments: Beck Depression Inventory, Geriatric depression scale, Centre for Epidemiological Studies scale on Depression and Hospital and Anxiety Depression Scale. Results : Overall prevalence of depression was 30%. Demographic variations and severity of COPD influenced prevalence. The inter-prevalence of the four screening tools was consistent. We found a low variation between studies using the same tool. Few studies used control groups or compared the screening tool to a psychiatrist evaluation. Conclusions : This article calls for further investigation of the association between COPD and depressive symptoms. The subject is highly relevant for everyday life of patients with COPD and attention needs to be drawn to this issue in both an out- and in-patients.